2009
DOI: 10.1007/s10461-009-9630-2
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Body Image Dissatisfaction and Depression on HAART Adherence in HIV Positive Men: Tests of Mediation Models

Abstract: The current study examined the role of body image dissatisfaction and depression on HAART adherence in a sample of HIV positive men. Participants were 124 HIV positive gay and bisexual men, who responded to an online survey. Results from moderated mediation models revealed that depression mediated the relationship between body dissatisfaction and HAART non-adherence for men who possessed elevated levels of body dissatisfaction, but not for those men who reported moderate or low levels. Additionally, depression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 46 publications
1
28
0
1
Order By: Relevance
“…There has been much less research conducted on body image and depression among sexual minority men. However, limited cross-sectional data have revealed that elevated body dissatisfaction is significantly associated with increased depressive symptoms among HIV-uninfected (e.g., Brennan, Craig, & Thompson, 2012) and HIV-infected sexual minority men (Blashill, Goshe, Robbins, Mayer, & Safren, 2014; Blashill & Vander Wal, 2010). For instance, Blashill (2010) found significant moderate-sized bivariate associations between higher body fat dissatisfaction/muscle dissatisfaction and elevated depressive symptoms among an Internet-based sample of gay and bisexual men, providing preliminary evidence that body dissatisfaction may serve as a risk factor for increased depression among sexual minority men.…”
Section: Introductionmentioning
confidence: 99%
“…There has been much less research conducted on body image and depression among sexual minority men. However, limited cross-sectional data have revealed that elevated body dissatisfaction is significantly associated with increased depressive symptoms among HIV-uninfected (e.g., Brennan, Craig, & Thompson, 2012) and HIV-infected sexual minority men (Blashill, Goshe, Robbins, Mayer, & Safren, 2014; Blashill & Vander Wal, 2010). For instance, Blashill (2010) found significant moderate-sized bivariate associations between higher body fat dissatisfaction/muscle dissatisfaction and elevated depressive symptoms among an Internet-based sample of gay and bisexual men, providing preliminary evidence that body dissatisfaction may serve as a risk factor for increased depression among sexual minority men.…”
Section: Introductionmentioning
confidence: 99%
“…Blashill and Vander Wal (2010) noted that the pressure to appear in shape and to project physical masculinity could facilitate HAART non-compliance. Galvan, Bogart, Wagner, and Klein (2012) found that, among 208 HIV+ Latino MSM, men endorsing traditional machismo (i.e., a cultural conceptualization of masculinity) were half as likely as others to report 100% adherence to medication.…”
Section: Resultsmentioning
confidence: 99%
“…Mais recentemente, foi descrito em homens infectados pelo HIV que a depressão é um importante mediador da relação entre a insatisfação com a imagem corporal e a má adesão à terapia antirretroviral 26 .…”
Section: I S C U S S ã Ounclassified